Pengaruh Promosi, Kualitas Pelayanan, dan Prosedur Pembiayaan terhadap Minat UMKM Blitar dalam Memilih Kredit Usaha Rakyat (KUR) Syariah Pegadaian - Rohmah Sabiq; Rachma Indrarini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of promotion, service quality, and financing procedures on the interest of MSMEs in Blitar in choosing Pegadaian’s Sharia People Business Credit (KUR). This research employs a quantitative method with a questionnaire as the data collection instrument. The sampling technique used is purposive sampling, involving 100 MSMEs in Blitar that meet the criteria. Data were analyzed using SEM-PLS version 4. The result show that promotion, service quality, and financing procedures have a positive and significant effect on the interest of MSMEs in Blitar in choosing Pegadaian’s Sharia KUR. Attractive promotions, quality service, and simple and fast procedures are the main strategies for increasing interest. Therefore, Pegadaian needs to optimize these strategies to enhance interest and expand MSMEs’ accessibility to sharia based financing.